(untitled) (International journal of artificial intelligence, 2024)
This article examines strategies for adapting to climate change and ensuring the rational use of natural resources in Uzbekistan. It highlights the challenges posed by rising temperatures, water scarcity, and desertification, while exploring practical solutions, including sustainable agriculture, renewable energy, and integrated water resource management. By analyzing Uzbekistan's policies and initiatives, the article offers insights into building resilience and promoting sustainable development in the face of climate challenges.